IMPROVEMENT OF COMPLEX COTTON OIL REFINING TECHNOLOGY - M.Х. Khamrakulova; D. Saydullayeva (Western European Studies, 2023)
This article comprehensively examines the economic repercussions resulting from the decrease in cotton cultivation in the Republic, particularly the subsequent reduction in processed seed production and its cascading effects on oil product availability. The decline has led to challenges in meeting local demand, necessitating the importation of oil products and soybeans, causing financial strain due to heightened reliance on foreign supplies and resultant price inflation. To address these challenges, the article highlights a strategic shift towards cultivating alternative oil crops better suited to the region's climate. However, the processing of these oilseeds predominantly occurs in smaller, specialized enterprises, posing operational difficulties for larger, less adaptable oil plants. A critical focus of the article revolves around the pressing need for advanced refining methodologies for crude oils. The current industrystandard practices, notably inefficient in purifying oils derived from lower-quality seeds, heavily rely on high-concentration alkali, resulting in substantial losses and increased production costs
Keywords: Oilseed Processing; Cotton Cultivation; Processed Seed